Diseño de estrategias comunicativas para sensibilizar a los usuarios del servicio de cedulación del registro civil sobre la importancia de la donación de órganos. - Bayas Jaramillo, Emilia Valeria (2015)
Communication for development opens the door to change in a society, and an integral part of their management, education becomes your best ally in building more ethical and socially conscious individuals that contribute to individual growth and community of a country. As part of an evolutionary process in society, communication for development arrises allowing the implementation of proposals directed to a change driven by and for the people, due to the broad scope that communication has and its importance within the society, it has been incorporated into other scientific and social fields. In the case of health communication works as a change manager and promoter of best practices that improve the quality and life expectancy of people. In Ecuador, several initiatives have been implemented by the state to promote the "Good Living" for communities, from this perspective, and in the field of health, after the assembly of Montecristi which reformed drastically and definitely the Constitution Ecuador, institutions like the INDOT and regulations as the Law on Donation and Transplantation of organs, tissues and cells, were created, which promotes organ and tissue donation as an altruistic and generous act that can save not one but several lives